A POSSIBLE MODALITY OF INTERVENTION IN A SURGICALLY IMPOSSIBLE CASE OF GIANT CORONARY ANEURYSM: A SUCCESSFUL CASE - Laksono, Sidhi; Jusuf, Axel; Kusharsamita, Hillary (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Giant coronary artery aneurysms (CAAs), defined as dilations exceeding 20 mm or four times the normal artery diameter, are rare clinical entities with limited management guidelines. Most cases are discovered incidentally, but complications can be life-threatening. Treatment remains controversial, with options including medical therapy, percutaneous intervention, and surgery. We report the case of a 64-year-old male with chest pain and high-risk NSTEMI, found to have a de novo giant saccular aneurysm in the mid-left anterior descending artery (LAD) through coronary CT angiography. Coronary angiography confirmed significant LAD and LCX stenosis alongside aneurysmal progression. Surgery was ruled out due to high intraoperative risk. After multidisciplinary deliberation, percutaneous coronary intervention (PCI) using overlapping covered stents was performed, successfully excluding the aneurysm. The patient’s condition stabilized post-procedure, and he was discharged in good condition with continued outpatient follow-up. This case demonstrates that percutaneous intervention with covered stents can be a safe and effective treatment for giant CAAs in select high-risk patients when surgical options are limited. It highlights the role of advanced imaging, intravascular ultrasound, and multidisciplinary decision-making in guiding individualized treatment. Further research is essential to establish optimal management strategies and long-term outcomes for patients with giant CAAs.